2017
DOI: 10.4314/as.v15i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorus and sulphur on dry matter yield of maize (<i>Zea mays</i>) in some soils at Abeokuta, Ogun State, Nigeria

Abstract: Pre-planting analyses were performed to determine soil pH, particle size, organic matter, K, Na, P and S. Eight weeks after planting, maize parts above the soil level were harvested, oven-dried and dry-matter yield were computed and recorded. Application of S fertilizer appears not to be critical to maize production in the study areas since singly added S did not produce significant increase in biomass yield. In contrast, applied P significantly increased MDY in all the soils except Obantoko II, which already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
4
5
0
Order By: Relevance
“…Phosphorus is essential for cell division and proper meristematic activity in plants. Therefore, the level of P in the growth medium of plants impacts their leaf color, leaf area, number of leaves, and seed and tuber development (Ogunsola and Adetunji 2016). Findings in this study where pig dung amendment significantly improved the yield and yield components of soybean is consistent with the report of Samuel et al (2018) who found that COCS amended with mammalian dung produced higher biomass and better quality bean crop than what was obtained from the untreated control experiment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Phosphorus is essential for cell division and proper meristematic activity in plants. Therefore, the level of P in the growth medium of plants impacts their leaf color, leaf area, number of leaves, and seed and tuber development (Ogunsola and Adetunji 2016). Findings in this study where pig dung amendment significantly improved the yield and yield components of soybean is consistent with the report of Samuel et al (2018) who found that COCS amended with mammalian dung produced higher biomass and better quality bean crop than what was obtained from the untreated control experiment.…”
Section: Discussionsupporting
confidence: 91%
“…This is congruent with Ikeogu and Nwaofia (2013) submission who also found these elements in low amounts in unamended soil of Umudike and Amakama, Southeast Nigeria. High aluminum toxicity, bio-unavailability of carbon, nitrogen and phosphorus characterize COCS, and these constraints were sufficiently overcome by pig dung amendments in a trial (Ojo-Omoniyi et al 2020). Findings in this study revealed increases in content of organic carbon, organic matter, K, P N in the amended COCS; harmonizing with reports of Ojo-Omoniyi et al (2020) who found these parameters to increase in COCS amended with pig dung.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The higher ear leaf content and lower limitation order of P under the NPKS is not surprising as P and S interact in synergy to influence uptake of each other. Studies in Nigeria by Ogunsola and Adetunji 50 recommended S application for enhanced P uptake by maize. The high recurrence of negative DRIS P balance index and increased order of P limitation for NPK and NPKB treatments is more difficult to explain, especially as P uptake is reported to be positively influenced by B application 51 .…”
Section: Discussionmentioning
confidence: 99%